Epidermal nevus of the hemithorax and upper limb with hyperplasia in the armpit - Ferrante, M. (European Journal of Pediatric Dermatology, 2017)
There are rare reports of epidermal nevi with exaggerate hyperkeratosis and papillomatosis (3) on the axillary region that are reminiscent of acanthosis migricans (2). Even a rounded and velvety axillary epidermal nevus has been identified as a separate entity (4). We believe that the particular environmental conditions of the folds can explain the greater evidence at this level of epidermal nevus and also of other diseases such as seborrhoeic warts, pemphigus vegetans, acanthosis nigricans and granular parakerotosis (1). The histologic absence of epidermolytic hyperkeratosis eliminates the possibility of epidermolytic ichthyosis in the offspring. However, we believe that other inherited skin disorders, such as erythrokeratoderma variabilis, may manifest themselves as epidermal nevus when they are due to a post-zygotic mutation and as generalized disease in the offspring in case of concomitant gonadal mosaicism.